The moderating role of Shariah compliance on the relationship between ethical commitment and corruption in Malaysian companies - Siti Nurain Muhmad; Ahmad Firdhauz Zainul Abidin; Siti Nasuha Muhmad; Ahmad Fadhli Mat Sidik (East Asian Economic Review (EAER), 2025)
Corporate ethics and corruption have garnered academic attention in recent decades. This study aims to gain insight into the relationship between ethical commitment and corruption and examine the moderating effect of Shariah compliance on this relationship. This study used 453 Malaysian companies from 2012 to 2021. The results indicate that a strong ethical commitment helps prevent management and employees from engaging in unethical behaviors that can lead to corruption within the company. However, the effect of ethical commitment on reducing corruption remains consistent, irrespective of a company's Shariah-compliant status. For the separating samples based on the pre- and post-Malaysian Code of Corporate Governance (MCCG) 2017, the result shows no differences in the relationship between ethical commitment and corruption. However, Shariah compliance companies were found to reduce corruption in the post-MCCG 2017 period. This implies that improving the corporate governance structure seems to better influence corruption levels in Shariah compliance companies. This study contributes to the growing literature on corporate ethics and corruption by empirically examining the role of ethical commitment in mitigating corruption within the context of Malaysian companies. It provides novel evidence on how Shariah compliance influences this relationship, particularly in light of recent regulatory changes brought about by the Malaysian Code of Corporate Governance (MCCG) 2017.
Keywords: D73; G38; M14; K42; 330; Ethical Commitment; Shariah-Compliance; Corruption